Inactivation Kinetics of Coxiella burnetii During High-Temperature Short-Time Pasteurization of Milk - Wittwer, Marcel; Hammer, Philipp; Runge, Martin; Valentin-Weigand, Peter; Neubauer, Heinrich; Henning, Klaus; Mertens-Scholz, Katja (Frontiers in Microbiology, 2022)
The Gram-negative, obligate intracellular bacterium Coxiella (C.) burnetii is the causative organism of the zoonosis Q fever and known for its resistance towards various intra- and extracellular stressors. Infected ruminants like cattle, sheep and goats can shed the pathogen in their milk. Pasteurization of raw milk was introduced for inactivation of C. burnetii and other milk-borne pathogens. Legal regulations for pasteurization of milk are mostly based on recommendations of the Codex Alimentarius. As described there, C. burnetii is considered as the most heat-resistant non-spore forming bacterial pathogen in milk and has to be reduced of at least 5 log10-steps during the pasteurization process. However, the corresponding inactivation data for C. burnetii originate from experiments performed more than 60 years ago. Recent scientific findings and the technological progress of modern pasteurization equipment indicate that C. burnetii is potentially more effectively inactivated during pasteurization than demanded in the Codex Alimentarius. In the present study, ultra-high heat-treated milk was inoculated with six different C. burnetii field isolates and high-temperature short-time heat-treated in a pilot plant. Kinetic inactivation data in terms of D- and z-values were determined and used to calculate extended inactivation curves. With regard to the mandatory 5 log10-step reduction of the pathogen, the efficacy of the established heat treatment regime was confirmed and, in addition, a reduction of 1 – 2 °C of the pasteurization temperature seems feasible.